Persepsi Keyakinan Kesehatan Memengaruhi Perilaku Wanita Usia Subur (WUS) Terhadap Pemeriksaan Inspeksi Visual Asetat (IVA) - Yhenti Widjayanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Cervical cancer is the most causa of deaths for women. Acetic Acid Visual Inspection Examination (IVA) is an effort to detect cervical cancer early. Conduct early detection is closely related to the perception of health beliefs (health belief). This study aimed to analyze the effect of perceived health beliefs on the behavior of women during childbearing age in conducting IVA examinations. The design of this study was observational analytic with a cross-sectional approach. The subjects of this study were 123 women who collected by simple random sampling. The variables of this study were the perception of health beliefs and behavior towards the IVA examination as early detection of cervical cancer. Data were collected by a questionnaire. The results showed that 57.7% of subjects had negative health belief perceptions, 60.2% had negative attitudes and 61.8% of subjects had never done an IVA examination. The results of the linear regression statistical test showed between the perception of health beliefs with attitudes obtained p-value = 0.00, the correlation value (R) = 0.951, the coefficient of determination = 0.904, between the perception of health beliefs with the act of conducting an IVA examination obtained p = 0.00, Correlation value (R) = 0.851 coefficient of determination = 0.724, It meant that there is an effect of perception of health beliefs on behavior (attitude & action) on IVA examination as early detection of cervical cancer. The implication in nursing is the need for collaboration between health cadres and the Public Health Center to increase socialization about IVA to women of childbearing age and family.